2004
DOI: 10.1111/j.1540-8159.2004.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Interatrial Conduction Delay:

Abstract: Atrial conduction disorders are frequent in elderly subjects and/or those with structural heart diseases, mainly mitral valve disease, hyperthrophic cardiomyopathies, and hypertension. The resultant electrophysiological and electromechanical abnormalities are associated with a higher risk of paroxysmal or persistent atrial tachyarrhythmias, either atrial fibrillation, typical or atypical flutter or other forms of atrial tachycardias. Such an association is not fortuitous because intra- and interatrial conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 152 publications
5
122
0
1
Order By: Relevance
“…15 Therefore, these results support the hypothesis that the P-A2 and the dispersion of P-A2 are partly determined by left atrial enlargement. According to Omi et al, the prolongation of P-A could be explained not only by left atrial enlargement but also by the time delay from atrial electric activation to myocardial contraction.…”
Section: The Correlationsupporting
confidence: 79%
“…15 Therefore, these results support the hypothesis that the P-A2 and the dispersion of P-A2 are partly determined by left atrial enlargement. According to Omi et al, the prolongation of P-A could be explained not only by left atrial enlargement but also by the time delay from atrial electric activation to myocardial contraction.…”
Section: The Correlationsupporting
confidence: 79%
“…The changes resulting in intra-and interatrial conduction delay can prepare convenient atrial substrate for AF. Anisotropy and dispersion of refractory periods resulting from the decrease in electrical connections and depositon of connective tissue between the myocytes cause atrial conduction abnormalities [8,20]. Cohen and Scherf [21] was first described the concept of interatrial block.…”
Section: Discussionmentioning
confidence: 99%
“…Among the noninvasive and invasive methods to evaluate the interatrial conduction, the basic and the most frequently used one is the electrocardiographic P wave duration and morphology [8]. Also, there are some echocardiographic methods to measure interatrial conduction times by the evaluation www.cardiologyjournal.org of cardiac electromechanical events.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the lengthening due to the P sense offset, one could hypothesize that larger atrial pacing percentages are found in sicker atria, showing delayed conduction. Similarly, evidence exists about a linear relationship between the degree of IACD and extent of left atrial mechanical dysfunction 2 . In this context we showed a higher prevalence of an important IACD in patients with sick sinus and bradycardia-tachycardia syndrome, in the elderly and in postoperative patients.…”
Section: Limitationsmentioning
confidence: 99%